The relationships between psychological safety and work engagement among Generation Z employees in the Jabodetabek area - Audry Carissa Dirk; Zamralita Zamralita; Reza Fahlevi (Privietlab, 2025)
Generation Z had just entered the workforce at a productive age. However, statistical data reveal that Generation Z is largely unemployed and is considered to have a lot of consideration of job selection due to the large amount of information spread and cultural changes, which makes Generation Z choose to quit work rather than carry out work that is not in accordance with their internal principles. A high quit rate is related to workers' work engagement. Early research has revealed that Generation Z has a low level of work engagement. The work engagement factor, psychological safety, is the belief that a safe work environment to be able to voice questions or suggestions without fear of negative consequences is also needed by Generation Z in their work. This study examined the relationship between psychological safety and work engagement experienced by Generation Z employees. Using a correlational quantitative method with convenience sampling technique, the participants were 210 Generation Z employees who worked in Jabodetabek at the age of 20–28 years, had at least high school/vocational school education, and had a minimum work experience of one year. Using measuring instruments Adaptation of the Psychological Safety Inventory (PSI) scale and the Utrecht Work and Well-Being Survey (UWES). The Spearman rank correlation test was used for data analysis. The results showed a positive relationship between psychological safety and work engagement among Generation Z employees in Jabodetabek (r = 0.504 and p < 0.05).